PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN BAGIAN PRODUKSI PADA PT.GEMA NUSA LESTARI MUARA TEMBESI - Ratna Ratna (Jurnal Ilmiah Universitas Batanghari Jambi, 2017)
This research was conducted at PT. Gema Nusa Lestari which is located at Jalan Sarolangun -Jambi District Amplu Muda Batang Hari Regency Jambi Province whose business activity is to manage timber to produce wood plywood. The purpose of this study is To know the motivation of work, work discipline, work productivity and there is influence of motivation and work discipline on employee productivity at PT. Gema Nusa Lestari in Muara Tembesi. The research method used in this research is a field research method. Further data collection techniques used by means of distributing questionnaires with population and sample sampling. Data analysis tool used is multiple regression analysis. Based on the analysis of reponden answers, obtained the result that the level of motivation, discipline and employee productivity is considered good. The results of this study indicate that there is influence of motivation and work discipline on employee productivity at PT. Gema Nusa Lestari in Muara Tembesi individually or simultaneously.Keywords: motivation, discipline and productivity